Pump it up : literacy activities for the classroom - Dowdy, Joanne Kilgour; Gao, Yang (Sense Publishers, 2016)
The book contributes to improving teaching and learning in a few ways: first, it provides in-service teachers with step-by-step, ready-to-use strategies that facilitate their students' comprehension and use of content area reading material; second, it aims to help pre-service teachers learn to implement hands-on lessons for their content area; third, apart from strategies offered to the content area teachers in the mainstream, the book also provides teachers of English language learners with strategies that address the literacy needs of their diverse students. "The authors in this collection offer teachers ways to deepen students' reading and writing engagement within particular content areas. These thoughtful lessons are ready to be implemented immediately in the classroom."--Denise N. Morgan, Ph. D., Kent State University "This book was created for teachers by teachers. It is filled with creative and engaging strategies, each having a step-by-step guide for implementation to promote student learning. Many of the strategies designed for specific content instruction can be modified for use across the curriculum. It is a refreshing compilation of instructional approaches and a valuable resource for both novice and veteran teachers."--Maria G. Dove, Ed. D., Molloy College "The book is not only a useful teaching manual for teachers in the USA, but also a helpful instructional guide for teachers from other cultures. Particularly for the last section on ESL/EFL learners, it provides teachers in the field with inspirational activities."--Haihua Wang, Ph. D., Dalian Maritime University